Halal Food and Safety Treands in 2021-2025 Era - Sutrisno Adi Prayitno; Noor Amirudin; Azril Akmad Nur Islami; Mochammad Taufik Yunus (PT. Gyandharma Global Media, 2025)
The halal food industry is experiencing rapid growth between 2021 and 2025, triggered by the increasing awareness of global consumers on the importance of food that is safe, healthy, and in accordance with ethical and religious principles. This article reviews the key trends and challenges in the halal industry, covering aspects of market growth, technological influence, and food safety issues. The increasing Muslim population and their purchasing power are the main drivers, along with non-Muslim consumers' interest in halal products. On the other hand, challenges such as disharmony in certification standards, product counterfeiting, and lack of experts are major concerns. Technologies such as blockchain, Internet of Things (IoT), and data analytics are solutions to improve transparency and traceability of the halal supply chain. The government and industry players are encouraged to collaborate in strengthening policies, regulations, and consumer education. In this digital era, the halal industry is no longer limited to fulfilling religious obligations, but rather a symbol of quality and global trust. Therefore, strengthening halal food safety aspects is the main strategy to answer market demands and maintain industry sustainability